Use of Gabapentin in the Treatment of Substance Use and Psychiatric Disorders: A Systematic Review - Ahmed, Saeed; Bachu, Ramya; Kotapati, Padma; Adnan, Mahwish; Ahmed, Rizwan; Farooq, Umer; Saeed, Hina; Khan, Ali Mahmood; Zubair, Aarij; Qamar, Iqra; Begum, Gulshan (Frontiers in Psychiatry, 2019)
Objective: Gabapentin (GBP) is a commonly used anticonvulsant and analgesic for the treatment of epilepsy and neuropathic pain. GBP is also frequently prescribed off-label for psychiatric disorders despite a lack of rigorous, comprehensive studies. However, there is growing evidence that GBP may be effective for the treatment of several of these indications. This review aimed to perform a systematic review of published literature on the efficacy of GBP in the treatment of various psychiatric illnesses and substance use disorders. Methods: This review was performed according to the PRISMA guidelines. The PubMed and Ovid MEDLINE databases were screened and filtered by using specific search terms and inclusion/exclusion criteria. The search terms generated 2,604 results, after excluding all duplicates and applying the inclusion/exclusion criteria, a total of 53 papers were retained for detailed review. Results: This literature review concludes that GBP appears to be effective in the treatment of various forms of anxiety disorders. It shows some effectiveness in bipolar disorder as an adjunctive therapeutic agent, while the evidence for monotherapy is inconclusive. In substance use disorders, GBP is effective for acute alcohol withdrawal symptoms with mild to moderate severity, it reduces cravings, improves the rate of abstinence and delays return to heavy drinking. GBP can be helpful for the treatment of opioid dependence, but there is limited evidence to support it. GBP may have therapeutic potential for cannabis use disorder. No significant effect of GBP use has yet been conclusively observed in the treatment of OCD, PTSD, depression, or cocaine and amphetamine abuse. Conclusion: GBP appears to be effective in the treatment of some forms of anxiety disorders, and alcohol withdrawals or dependence, albeit it is effective often as an adjunctive medication rather than as a monotherapeutic agent. More rigorous larger clinical trials are required to resolve the contradictory existing data for the efficacy of GBP. It is worth noticing that numerous clinical studies on this subject are open-label trials, which are inherently less rigorously analyzed. Therefore, more extensive large randomized controlled trials are required to examine not only the effectiveness of GBP but also its safety and tolerance.